2004
DOI: 10.1177/0256090920040105
|View full text |Cite
|
Sign up to set email alerts
|

Business Process Outsourcing (BPO): Emerging Scenario and Strategic Options for IT-enabled Services

Abstract: The paradigm shift that the Internet has brought about in communication has opened up a plethora of opportunities for outsourcing business processes (BPO) across continents. Success lessons in manufacturing sub-contracting are found to be relevant for understanding the logic of BPO. Outsourcing involves transferring certain value contributing activities or processes to another firm to save costs and for the principal to focus on its areas of key competence. The possibilities of disaggregating value elements fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…Similarly, outsourcing to India can free up $30 billion for new investments in the US (The Economic Times, 2005). This is primarily due to an estimated 30-50 per cent cost saving, software development and the availability of thousands of well-trained professionals who can speak fluent English (see Chengappa and Goyal, 2002;Ramchandran and Voleti, 2004;Saini and Budhwar, 2004). The CC sector in India is projected to have a tremendous future.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, outsourcing to India can free up $30 billion for new investments in the US (The Economic Times, 2005). This is primarily due to an estimated 30-50 per cent cost saving, software development and the availability of thousands of well-trained professionals who can speak fluent English (see Chengappa and Goyal, 2002;Ramchandran and Voleti, 2004;Saini and Budhwar, 2004). The CC sector in India is projected to have a tremendous future.…”
Section: Introductionmentioning
confidence: 99%
“…Bowersox Evans and Shulman, 1992). Acknowledging the dramatic changes in the economy, which has become more information intensive, more global and more dependent on technology, several authors, both inside and outside the logistics discipline, have indicated the importance of logistics as a source of sustainable competitive advantage (Achrol, 1991;Day, 1994;Porter, 1985; Stalk, Evans and Shulman, 1995; Yin, 2009).…”
Section: Logistics Issues and Analysesmentioning
confidence: 99%
“…The different types of knowledge work that go into a BPO can be broadly categorized as (Ramachandran and Voleti, 2004) are (1) Data entry and conversion which includes medical transcription; (2) Rule Set Processing in which the information worker makes judgement based on a set of rules provided by the client; (3) Problem solving in which the information worker has more discretion, the rules here are fluid and less amenable to structuring than in the rule-set processing genre; (4) Direct customer interaction in which the information worker handles more elaborate interaction with the client's customers; and (5) Expert 'knowledge services' which require specialists and are similar to services offered by consultants.…”
Section: Introductionmentioning
confidence: 99%
“…In general, SOP enable increased flexibility by freeing valuable staff resources to do what may be required best at a particular business juncture and relocating business capital to procure/develop valuable resources. Flexibility is further enhanced through 24/7 (i.e., round-the-clock all week) operating hours that ensure continuous support through integrated in-house and offshore based staff in other time zones [27].…”
Section: Transformational Partnershipmentioning
confidence: 99%